215 The utility of a personalised risk calculator in gynae-oncology surgery. (4th December 2020) - Jones, Sadie; Murray, Ines; Lim, Kenneth; Howells, Robert; Jones, Rhidian; Sharma, Aarti
Abstract : Introduction/Background: The objective of this study was to examine the clinical utility of the American College of Surgeons (ACS) surgical risk calculator, developed as part of the National Surgical Quality Improvement Programme (NSQIP), in predicting perioperative morbidity in gynae-oncology patients, primarily, as a prediction model and secondly, as a tool to identify patients who are at increased risk of developing complications. Methodology: A retrospective review of 142 patients who underwent major surgery under the gynae-oncology team between 06/08/2018–16/04/2019 at the University Hospital of Wales. Pre-operative factors combined with a procedure-specific code generated the predicted risk of 13 post-operative complications for each patient. Brier scores assessed calibration and receiver operated curves (AUC) evaluated the discriminative power of NSQIP. Results: Complications were experienced by 35.2% (50/142) patients. The calculator displayed adequate calibration when used to predict serious complications (Brier = 0.070), readmission (Brier = 0.058), return to OR (Brier = 0.000) and UTI (Brier = 0.001). It had the greatest discriminative power when predicting the risk of serious complications (AUC = 0.672; 95% CI, 0.481–0.863). The calculator successfully identified a majority of patients who had a complication as being of 'above average risk' for all complications, apart from return to OR, based on their pre-operative factors. Conclusion: NSQIP has previously been demonstrated to be a useful pre-operative tool for evaluating the risk of post-operative complications in colorectal surgery. This study suggests that in the setting of gynae-oncology surgery the calculator does not have adequate discriminative power to be an absolute predictor of all complications, however, it may be useful in identifying patients who are likely to develop serious complications and those at above average risk of complications. Disclosures: Inés Murray – I can confirm that I have no conflict of interest with reference to this work. Kenneth Lim – I can confirm that I have no conflict of interest with reference to this work. Robert Howells – I can confirm that I have no conflict of interest with reference to this work. Rhidian Jones – I can confirm that I have no conflict of interest with reference to this work. Aarti Sharma – I can confirm that I have no conflict of interest with reference to this work. Sadie Jones - I can confirm that I have no conflict of interest with reference to this work.